PERAN AKUNTANSI PADA TINGKAT PENGGUNAAN INFORMASI AKUNTANSI BERBASIS DIGITAL DAN KINERJA UMKM - Annisa Tiara Rahmawati Annisa; Irzan Irzan; Rebi Rahmad Ramadan (Universitas Muhammadiyah Bengkulu, 2024)
The role of accounting in utilizing all information and knowledge related to digital-based accounting information and technology is very necessary, especially for business actors who will run digital-based businesses in the future. So this research aims to find out how big the role of accounting is in the level of use of digital-based accounting information and the performance of MSMEs. The technique used in this research uses the Systematic Literature Review (SLR) method. In this research, the articles obtained were 30 articles indexed by Sinta. The results of the analysis show that the role of accounting and the use of digital-based accounting information systems has a positive influence on the performance of SMEs and the performance of SMEs has a positive influence on the use of accounting information. Keywords: Role of Accountants, Digitalization, MSME Performance